Satellite stories: capturing professional experiences of academic health sciences librarians working in delocalized health sciences programs. - Phinney, Jackie; Horsman, Amanda Rose (Journal of the Medical Library Association, 2018)
Objective: Health sciences training programs have progressively expanded onto satellite campuses, allowing students the opportunity to learn in communities away from an academic institution's main campus. This expansion has encouraged a new role for librarians to assume, in that a subset of health sciences librarians identify as "satellite librarians" who are permanently located at a distance from the main campus. Due to the unique nature of this role and lack of existing data on the topic, the authors investigated the experiences and perceptions of this unique group of information professionals. Methods: An electronic survey was distributed to health sciences librarians via two prominent North American email discussion lists. Questions addressed the librarians' demographics, feelings of social inclusion, technological support, autonomy, professional support, and more. Results: Eighteen surveys were analyzed. While several respondents stated that they had positive working relationships with colleagues, many cited issues with technology, scheduling, and lack of consideration as barriers to feeling socially included at both the parent and local campuses. Social inclusion, policy creation, and collection management issues were subject to their unique situations and their colleagues' perceptions of their roles as satellite librarians. Conclusions: The results from this survey suggest that the role of the academic health sciences librarian at the satellite campus needs to be clearly communicated and defined. This, in turn, will enhance the experience for the librarian and provide better service to the client.